INFLUENCE OF BUSINESS EDUCATION ON ENTREPRENEURIAL INTENTION WITH FEASIBILITY AND ENTREPRENEURIAL SELF-EFFICACY AS INTERVENING VARIABLES - Marlina Deliana; Kusdi Rahardjo; Tri Wulida Afriyanti (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2019)
This aims to examine the effect of business education on entrepreneurial intention with feasibility and entrepreneurial self-efficacy as the intervening variables. This study was conducted on students of Business study programs, Faculty of Administrative Sciences, Universitas Brawijaya (FIA UB). The number of samples used in this study was 321 students using proportionate stratified random sampling. The questionnaire was used to collect data, and Partial Least Square (PLS) was used for the analysis. We found that; business education has a positive effect on feasibility; business education has a positive effect on entrepreneurial self-efficacy; feasibility has a positive influence on entrepreneurial intention; entrepreneurial self-efficacy has a positive influence on entrepreneurial intention; entrepreneurial self -efficacy has a positive influence on feasibility; and business education has a positive influence on entrepreneurial intention, both directly and indirectly through feasibility and entrepreneurial self-efficacy. The results of this study are expected to provide insight into the feasibility and entrepreneurial self-efficacy so that students can improve these aspects to start a business.